Efektivitas manajemen sumber daya manusia dalam meningkatkan profesionalisme guru - Nafia, Jilan (Maliki Interdisciplinary Journal, 2025)
Education Teacher professionalism is a crucial supporting the quality of education. As it is directly related to competence, responsibility, and integrated in carrying out duties. Human Resource Management (HRM) includes planning, recruitment, training, career development, performance appraisal, and rewards. Well-planned and structured HRM can serve as a key strategy in shaping professional, competence, and high-quality teachers. Ongoing training programs and fair evaluation systems, encourage teachers to continue growing and innovating in the learning process. A positive work environment also contributes to teacher professionalism and can enhance the overall quality of education. Therefore, improving HRM in an important investment in the long-term development of better education quality.